A two-stage optimization model for the synthesis of biochar-based carbon management networks - Belmonte, Beatriz A. (Animo Repository, 2017)
Biochar, a product obtained from pyrolysis of residual biomass, can be deliberately applied to soil to sequester carbon from the atmosphere and simultaneously improve soil fertility. These benefits can be potentially scaled up through biochar-based management networks. Such systems have a potential to store carbon dioxide in the long run and can thus contribute significantly to mitigate global climate change. These systems pave the way to systematically allocate biochar streams of different quality levels to various sinks, such as agricultural lands which may have tolerance limits on the amount of contaminants in biochar. In this work, a two-stage optimization model is proposed to determine the source-sink allocation of biochars while simultaneously ensuring that the land's quality requirements are attained. In the first stage, the system's total cumulative CO2 sequestration is maximized. Then, a cost equation is incorporated in the model to minimize the system's total cost within the given time frame. A case study is solved to demonstrate the applicability of the developed model. Copyright © 2017, AIDIC Servizi S.r.l.